Self‐reported sleep patterns and quality amongst adolescents: cross‐sectional and prospective associations with anxiety and depression. (17th June 2020) - Orchard, Faith; Gregory, Alice M.; Gradisar, Michael; Reynolds, Shirley
Abstract : Background: Sleep problems are common in adolescence, and frequently comorbid with both anxiety and depression. Research studies have suggested a bidirectional relationship between sleep and psychopathology, which includes evidence that sleep interventions can alleviate symptoms of anxiety and depression. However, little is known about the nature of sleep problems amongst adolescents with anxiety and depression, and whether specific sleeping difficulties are involved in the longitudinal relationship between sleep, anxiety and depression. Method: The sample was derived from the Avon Longitudinal Study of Parents and Children (ALSPAC), a population‐based, prospective, birth cohort study of children born in 1991–1992. Data were explored from a subset of participants who took part in a clinical assessment at age 15, on self‐report sleep patterns and quality, and diagnostic outcomes of anxiety and depression ( N = 5, 033). Subsequent diagnostic and symptom severity data on anxiety and depression at ages 17, 21 and 24 were also examined. Results: Cross‐sectional and longitudinal analyses were conducted to explore the relationship between sleep problems, anxiety and depression. Results revealed that adolescents aged 15 with depression experience difficulties with both sleep patterns and sleep quality, whereas adolescents with anxiety only reported problems with sleep quality. A range of sleep variables at age 15 predicted the severity of anxiety and depression symptoms and the diagnoses of anxiety and depressive disorders at age 17, 21 and 24 years. Conclusions: The results provide further insight into the nature of sleep problems amongst adolescents with anxiety and depression, and the prospective relationship between sleep disturbance and future psychopathology. These data suggest that targeting sleep difficulties during adolescence may have long‐term mental health benefits.